The Application of Discovery Learning Model with Reward for Improving the Learning Activities of Biology Studens in Class XI MIA 2 SMAN 1 Padang - Zul Yusri; Putri Putri (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
Student activity is an important factor that must be a concern in the learning process, especially in biology subjects which have tended to be considered as many memorized and Latin subjects. One effort that can be done to improve student learning activities is through the application of discovery learning models along with the provision of rewards with the material used, namely animal networks. The purpose of this study was to improve the learning activities of Biology students in class XI MIA 2 SMAN 1 Padang. This type of research is Classroom Action Research (CAR) which was conducted in two cycles consisting of four stages, namely planning, implementing, observing, reflecting. namely students of class XI MIA 2 SMAN 1 Padang the number of students as many as 29 people. Data collection techniques were obtained through observation, questionnaires. The results showed that the application of discovery learning learning models can improve the learning activities of Biology students in animal network material. students are classified as good from 67.93% in Cycle I, increased to 78.62% in Cycle II, and increased by 10.72%.